2009
DOI: 10.1007/s00213-009-1493-8
|View full text |Cite
|
Sign up to set email alerts
|

Depression-like deficits in rats improved by subchronic modafinil

Abstract: The improvement of impaired attentional and information-processing functions under depression-like conditions suggests a benefit of modafinil in treatment of cognitive residual symptoms in affective disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Modafinil has been shown to exert antidepressive effects [4] and like other stimulants is an effective adjuvant for those experiencing only marginal improvement with serotonergic compounds [5], [6]. Classical psychostimulants, such as dextroamphetamine and methylphenidate exhibit dose-dependent biphasic effects on cognition—enhancing performance, learning and memory consolidation at moderate doses, but impairing cognitive function when used at high doses [7][9].…”
Section: Introductionmentioning
confidence: 99%
“…Modafinil has been shown to exert antidepressive effects [4] and like other stimulants is an effective adjuvant for those experiencing only marginal improvement with serotonergic compounds [5], [6]. Classical psychostimulants, such as dextroamphetamine and methylphenidate exhibit dose-dependent biphasic effects on cognition—enhancing performance, learning and memory consolidation at moderate doses, but impairing cognitive function when used at high doses [7][9].…”
Section: Introductionmentioning
confidence: 99%
“…[39] The mouse forced swimming test [45] and the tail suspension test [46] have been used to provide evidence of antidepressant activity for most approved antidepressants. Various agents such as modafinil, [47] ropinirole [41] and bromocriptine [42] that enhance dopamine transmission show antidepressant activity (i.e. decrease immobility time) in these animal models.…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Likewise, modafinil, a nonamphetamine stimulant commonly prescribed for the treatment of narcolepsy and daytime sleepiness (Ballon and Feifel 2006;Becker et al 2004;McClellan and Spencer 1998;Thorpy et al 2003), has positive effects on ADHD symptoms (Rugino and Copley 2001;Taylor and Russo 2000;Turner et al 2004) and can enhance attentional and working memory performance in healthy participants (Baranski et al 2004;Dodds et al 2009;Müller et al 2004; Thomas and Kwong 2006;Turner et al 2003a;Wesensten 2006;Winder-Rhodes et al 2009; see Minzenberg and Carter 2008, for a review). Animal studies have also revealed improvement in depression-like attention deficits (Regenthal et al 2009). However, several studies found no effects on sustained attention, spatial span and higher-order executive functions (Müller et al 2004;Randall et al 2003Randall et al , 2005aTurner et al 2003b), whilst beneficial effects might be restricted to low-performing participants (Müller et al 2004;Randall et al 2005b).…”
Section: Introductionmentioning
confidence: 96%